Peningkatan Pengetahuan tentang Pemilihan Makanan untuk Manajemen Cedera pada Atlet Sepak Bola Junior di PS Sleman Development Center - Sari, Siska Puspita; Afriani, Yuni; Sucipto, Adi; Puspaningtyas, Desty Ervira (Jurnal Gizi, 2023)
One of the causes of improper nutritional intake of athletes is that athletes have not received education/knowledge about nutrition in sport performance for athletes. Inadequate nutritional intake of athletes is one of the triggers for fatigue and risk of injury. This activity aims to increase to knowledge and attitudes of athletes regarding proper nutritional intake and proper handling of injuries in athletes. Community service activities are carried outthrough education and simulation of food and drink selection in handling injuries to athletes, as many as 22 PS Sleman Development Center athletes who are members of the U-16 groups on 7 July 2022 at Macanan Squarem Prambanan, Yogyakarta . Community service activities are carried out in several stages in their implementation, starting from preliminaru studies,coordination with coaches, making materials, simulating food dan drink selection in handling athlete’s injuries. The increase in knowledge was measured from the average value of the pretest before being given educational on question number 2, which was 72,64 and after being given education it increased to 81,72. The increase in knowledge was measuredfrom the average value of the pretest before being given educational on question number 5, which was 90,8 and after being given education it increased to 95,34. The maximun posttest score at the end of session after being given education is 80 with a minimum score of 20. Nutrition education activities for athletes are expected to be carried out on an ongoing basisas an effort to assist appropriate nutritional interventions for athletes, especially when athletes experience injuries. Keywords: Knowlegde, Eating Selection, Injury, Football Athletes